Pengaruh Liquidity, Leverage, Company Efficiency, Sales Growth, Firm Size, dan Market Power Terhadap Profitabilitas Perusahaan Pada Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2018-2022 - Parlaungan Putri, Gabriella Alneivadha; Meidiaswati, Harlina (Universitas Negeri Surabaya, 2025)
This study aims to determine the effect of liquidity, leverage, company efficiency, sales growth, firm size, market power on company profitability as measured by Return on Asset (ROA). The study population is agricultural sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The sample was taken by purposive sampling to obtain 16 companies. The analysis technique used is multiple linear regression. The results of the study indicate that liquidity has a significant negative effect on company profitability, leverage does not affect company profitability, company efficiency has a significant positive effect on company profitability, sales growth does not affect company profitability, firm size does not affect company profitability, and market power has a significant positive effect on company profitability. Based on these results, companies are advised to balance between adequate liquidity and efficient use of funds, companies must also utilize their assets efficiently to increase their productivity, and need to strengthen their position in the market to maintain competitive advantage.